Toward Reproducible Environmental Modeling for Decision Support: A Worked Example - White, Jeremy T.; Foster, Linzy K.; Fienen, Michael N.; Knowling, Matthew J.; Hemmings, Brioch; Winterle, James R. (Frontiers in Earth Science, 2020)
A fully-worked example of decision-support-scale uncertainty quantification (UQ) and data assimilation (DA) is presented. The analyses are implemented for an existing groundwater flow model of the Edwards Aquifer, Texas, USA, and are completed in a script-based workflow that strives to be transparent and reproducible. High-dimensional parameter DA is used to history-match simulated outputs to corresponding state observations of spring discharge and groundwater level. Then a hindcast of a historic drought is made. Using available state observations recorded during drought conditions, the combined UQ and DA analyses are shown to yield an ensemble of model results that bracket the observed hydrologic responses. All files and scripts used for the analyses are placed in the public-domain to serve as a template for other practitioners who are interested in undertaking these types of analyses.